Dynamics of lipids and metabolites during the cell cycle of Chlamydomonas reinhardtii. (8th September 2017) - Jüppner, Jessica; Mubeen, Umarah; Leisse, Andrea; Caldana, Camila; Brust, Henrike; Steup, Martin; Herrmann, Marion; Steinhauser, Dirk; Giavalisco, Patrick
Summary: Metabolites and lipids are the final products of enzymatic processes, distinguishing the different cellular functions and activities of single cells or whole tissues. Understanding these cellular functions within a well‐established model system requires a systemic collection of molecular and physiological information. In the current report, the green alga Chlamydomonas reinhardtii was selected to establish a comprehensive workflow for the detailed multi‐omics analysis of a synchronously growing cell culture system. After implementation and benchmarking of the synchronous cell culture, a two‐phase extraction method was adopted for the analysis of proteins, lipids, metabolites and starch from a single sample aliquot of as little as 10–15 million Chlamydomonas cells. In a proof of concept study, primary metabolites and lipids were sampled throughout the diurnal cell cycle. The results of these time‐resolved measurements showed that single compounds were not only coordinated with each other in different pathways, but that these complex metabolic signatures have the potential to be used as biomarkers of various cellular processes. Taken together, the developed workflow, including the synchronized growth of the photoautotrophic cell culture, in combination with comprehensive extraction methods and detailed metabolic phenotyping has the potential for use in in‐depth analysis of complex cellular processes, providing essential information for the understanding of complex biological systems. Significance Statement: Metabolites are the building blocks constituting the bases for all cellular processes. Determining their concentrations therefore provides insight into the networks regulating cellular growth and development. In the current paper we established a workflow for a multi‐omics‐based analysis of multiple molecular features using homogenously synchronized Chlamydomonas cultures. The proof of concept analysis of the extracted metabolites and lipids clearly provides insights into the time‐resolved dynamics of these compounds during the diurnal cell cycle.